Roles of organokines in intervertebral disc homeostasis and degeneration - He, Yuxin; Liu, Sheng; Lin, Hui; Ding, Fan; Shao, Zengwu; Xiong, Liming (Frontiers in Endocrinology, 2024)
The intervertebral disc is not isolated from other tissues. Recently, abundant research has linked intervertebral disc homeostasis and degeneration to various systemic diseases, including obesity, metabolic syndrome, and diabetes. Organokines are a group of diverse factors named for the tissue of origin, including adipokines, osteokines, myokines, cardiokines, gastrointestinal hormones, and hepatokines. Through endocrine, paracrine, and autocrine mechanisms, organokines modulate energy homeostasis, oxidative stress, and metabolic balance in various tissues to mediate cross-organ communication. These molecules are involved in the regulation of cellular behavior, inflammation, and matrix metabolism under physiological and pathological conditions. In this review, we aimed to summarize the impact of organokines on disc homeostasis and degeneration and the underlying signaling mechanism. We focused on the regulatory mechanisms of organokines to provide a basis for the development of early diagnostic and therapeutic strategies for disc degeneration.